Visible utterance: aspects of visuality in Е. E. Cummings’ poetics (Philology, 2026)
The study focuses on the visual aspects of the poetics of the American poet and painter E. E. Cummings. It accentuates on the author’s “awareness” of the integral “wholeness” of his artistic personality. Some governing esthetic principles underlying E. E. Cummings’ oeuvre are explored together with the verbo-visual “toolbox” of techniques E. E. Cummings utilizes to impact his readers’ perceptions. Through the analysis of particular visual poems the paper elucidates the strategies E. E. Cummings employs to control the pace and tempo of the reception of his works.
Keywords: E. E. Cummings; poetics; visual poetry; language of gesture